F1 POWER BOAT:Strategi Diplomasi Indonesia Dalam mencapai tujuan SDG's pada visi 2030 - Fuji Santoso; Ibnu Zulian (JOSH: Journal of Sharia, 2025)
This study analyzes sports diplomacy through the F1 Power Boat event on Lake Toba as part of Indonesia's efforts to support the achievement of the Sustainable Development Goals (SDGs) in Indonesia's Vision 2030. The study uses a descriptive qualitative approach based on secondary data from policy documents, official reports, and academic literature. The results show that the F1 Power Boat event serves as an effective soft power diplomacy instrument in improving Indonesia's image and strengthening tourism nation branding. This event also contributes to the achievement of SDGs 8, SDGs 9, and SDGs 11 through improving the local economy, developing infrastructure, and strengthening priority tourism destinations. In addition, the F1 Power Boat event encourages synergy between diplomacy, tourism, and regional economic development. However, the sustainability of its impact depends on sustainable governance and attention to social and environmental aspects. Overall, sports diplomacy through the F1 Power Boat event has the potential to be an effective strategy in supporting sustainable development and Indonesia's Vision 2030 if managed in an integrated and long-term manner.